보편적 학습 설계에 근거한 영어과 디지털 교과서 개선 방안 - 김정렬(Jeong-ryeol Kim) (한국콘텐츠학회 논문지, 15(7), 2015)
One of the issues with the textbooks pertinent to the current study is whether or not the Universal Design for Learning (UDL) factors have been dealt to satisfy students with different aptitudes in learning the core objectives of the lessons. This study develops a modified version of the UDL analysis criteria from the cross curricular criteria to language teaching and learning and uses it to analyze the sequence of digital English textbooks to investigate the descriptive statistics of the UDL factors in the new textbooks. The result shows that the textbook is designed most favorably to the students with the talent of linguistic aptitude and less favorably to the students with other types of aptitudes. The sequence analysis shows that sentence/word length and appearance of new words are incrementally sequenced as students advance upper grades. However, the syntactic complexity of middle school curves up steeply which is different from the elementary school textbooks. The UDL analysis will provide learning factors to consider when designing digital English textbooks to cover different aptitudinal groups. 본 연구의 목적은 보편적 학습 설계 준거를 제시하고 이 준거를 활용하여 현재 실험학교에서 운용되고 있는 영어과 디지털교과서를 분석함에 있다. 보편적 학습 설계 준거를 기준으로 디지털 교과서가 학년과 학급급간에 의사소통기능별로 어떠한 양상을 보이고 있는지를 분석하여 디지털 교과서의 개선 방향을 모색하고자 한다. 디지털 교과서의 분석 결과를 살펴보면 우선 학습자들 중에 언어적 적성이 있는 학생들에게 친화적인 환경으로 구성되어 있고 다른 적성의 학생들은 불리하게 구성되어 있어서 이를 보완할 필요가 있다. 어휘의 계열성은 학년이 올라감에 따라서 적절하게 복잡도가 증가하고 있으나 통사적 복잡성은 중학교에서 갑자기 문장당 어휘수가 급격하게 올라가면서 보편적 학습 설계 준거를 만족시키지 못하고 있어서 이에 대한 보완이 시급하다. 서책형 교과서와 달리 디지털 교과서는 멀티미디어 자원의 통합이 용이하고 볼륨의 제한을 받지 않기 때문에 근본적으로 디지털 교과서를 구성할 때에 이를 사용하는 학습자들이 가진 언어적 적성 외에 다양한 적성을 고려할 필요가 있다.